1997
DOI: 10.1002/(sici)1097-0185(199703)247:3<432::aid-ar16>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of a six‐legged goat with duplication of the intestinal, lower urinary, and genital tracts

Abstract: Background: An adult female goat with rare malformations, which consisted of duplication of the intestinal, lower urinary, and genital tracts as well a pair of parasitic appendages, is presented.Methods: A complete dissection was performed on a moribund female goat (Capra hircus).Results: The animal had a normal body with a parasitic attachment located within the pelvic region. This attachment was represented by an ovoid, trunk-like, adipose mass that lacked internal organs or vertebrae but that had two fairly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The predominant or absolute presence of adipose tissue is species wide in asymmetric twinning. EHT are not an isolated phenomenon of humans, they have also been described in goats and sheeps [10,29]. Thus, Otiang'a-Owiti et al [29] reported on an adult female goat (Capra hircus) showing duplication of the intestinal, lower urinary and genital tracts as well a pair of parasitic appendages.…”
mentioning
confidence: 99%
“…The predominant or absolute presence of adipose tissue is species wide in asymmetric twinning. EHT are not an isolated phenomenon of humans, they have also been described in goats and sheeps [10,29]. Thus, Otiang'a-Owiti et al [29] reported on an adult female goat (Capra hircus) showing duplication of the intestinal, lower urinary and genital tracts as well a pair of parasitic appendages.…”
mentioning
confidence: 99%